Environmental Threats to the Symbiotic Relationship of Coral Reefs and Quorum Sensing - Generous, Rochanya A (Consilience, 2014)
The coral reefs are declining in vitality and quantity in all parts of the world. Microbiomes exist symbiotically on the individual coral polyps. With this understanding comes the idea that microbiomes may coordinate survival through their inhabiting microbe colonies in order to sustain the life of the coral polyps. Of particular interest is quorum sensing, a form of bacterial communication known to coordinate gene expression in density dependent bacteria. The importance of understanding the symbiotic relationship between microbe’s use of quorum sensing and the coral it inhabits may offer insight in how microbiological colonies promote reef health and how external toxins alter these molecular processes.